#TITLE_ALTERNATIVE# - WAHYUNI (NIM 20107068), IKA
Optimal harvesting of prey in predator prey ecosystem is studied under the condition that the existence of the predator has been maintained. Human and bird, act as predator compete for fish. The behaviour of the system is studied and condition for optimal control are proposed. Various optimal harvest rate are investigated for particular ecosystem characteristic, such as harvesting costs, the discount rate value, and value functions for birds. The approach path towards an optimal regime is shown qualitatively and consists of an alternating choice between harvesting maximally and not harvesting.